Antioxidant Activity of Syzygium polyanthum Wight Extracts - Mutia Devi Hidayati; Taslim Ersam; Kuniyoshi Shimizu; Sri Fatmawati (Indonesian Journal of Chemistry, 2017)
Antioxidant activities of Syzygium polyanthum Wight leaves extracts (methanol, ethyl acetate, dichloromethane, and hexane) were evaluated by using DPPH (2,2-diphenyl-2-picrylhydrazyl hydrate) and ABTS (2,2’-azinobis (3-ethylbenzothiazole-6-sulfonic acid) methods.  The methanol extract showed the highest antioxidant activity of DPPH assay among extracts with IC50 value of 55.2 mg/ml.  In addition, methanol extract also showed the highest antioxidant activity of ABTS assay among extracts with IC50 value of 17.41 mg/ml. It indicated that methanol extract of S. polyanthum Wight leaves potential for antioxidant.